1997
DOI: 10.1002/(sici)1099-1611(199703)6:1<65::aid-pon236>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

A Psychosocial Intervention for Patients with Soft Tissue Sarcoma

Abstract: Support groups have increasingly been demonstrated to be an effective intervention in reducing psychological difficulties and emotional problems in patients with cancer. This report describes a pilot support group intervention based upon a modified version of Cain and collleagues' (1986) thematic counseling model for patients who have been treated for soft tissue sarcoma and are free of disease. The modified thematic counseling model consisted of eight group sessions that focused on providing information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…These findings are consistent with Payne et al [67] and Roberts et al [68] who demonstrated that support groups lead to a sense of belonging and empathy through identification with others in the same situation. Participants in a study by Malcomson et al [69] identified the positive nature of social interaction with others with MS in sharing experiences and advice, and dispelling worries.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with Payne et al [67] and Roberts et al [68] who demonstrated that support groups lead to a sense of belonging and empathy through identification with others in the same situation. Participants in a study by Malcomson et al [69] identified the positive nature of social interaction with others with MS in sharing experiences and advice, and dispelling worries.…”
Section: Discussionsupporting
confidence: 91%
“…d corresponds to the within‐group change (or difference) score, where D = X 1 – X 2 and d = Mean D /SD D . Cohen categorized d scores of 0.2 as small, 0.5 as moderate, and 0.8 as large …”
Section: Resultsmentioning
confidence: 99%
“…The supportive psychotherapy intervention (SGP) utilized as the comparison was based on the model developed by Cain et al [30] and manualized by Payne et al [31]. The eight weekly 90-min sessions focused on discussion of issues themes that emerge for patients coping with cancer.…”
Section: Supportive Psychotherapymentioning
confidence: 99%